Perbandingan Efek Core Exercise dan Balance Strategy Exercise Terhadap Kekuatan Otot Tungkai dan Keseimbangan Dinamis pada Lansia - Ilham Shyko Imama; Awal Prasetyo; Renni yuniati (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The main problem that is often experienced by the elderly around the world is falls. where the incidence of falls is one of the factors in death due to injury, the high risk of falls is due to lack of physical activity. this is due to the complex and multipathological risk factors for falls, so it is necessary to practice simple effective and efficient physical activity that can be done alone and does not cost money. This study is an experimental study with a design in the form of Pre and Post Test Control Group Design. This research was conducted at the Potroyudan elderly service centre in Jepara, Central Java. The population of this study was 85 people. Sampling purposive sampling method as many as 40 people divided into 2 groups. Grouping of samples is done randomly / randomly, data analysis using paired sample t test and Independent T Test, The results showed an increase in dynamic balance and leg muscle strength after being given core stability exercise and balance strategy exercise. The results of the comparison of dynamic balance showed no significant difference. The results of the comparison of leg muscle strength showed a significant difference in the increase in leg muscle strength.core exercise is better in increasing leg muscle strength in the elderly